2016
DOI: 10.1515/ijcre-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation Efficiencies in a Photo-CREC Water-II Reactor Using Several TiO2 Based Catalysts

Abstract: This study reports phenol degradation using several TiO2 photocatalysts (DP25, Anatase 1, Hombikat UV-100, Anatase 2) in a Photo-CREC Water-II Reactor. The physicochemical properties of the photocatalysts used, such as crystallinity, superficial area, and pore size distribution are reported. Reactor efficiencies are calculated using both Quantum Yields (QYs) and Photochemical and Thermodynamic Efficiency Factors (PTEFs). This is accomplished using phenol and phenol intermediate photoconversion rates. This allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The quantum yield definition established for the photoconversion of chemical species ,,, has to be modified for hydrogen production. As reported in eq , the φ H 2 shall involve H • radicals, which are the primary chemical species leading to the formation of H 2 as follows Thus, the φ H 2 accounts for hydrogen production as a ratio of the H • radical species produced over the number of photons absorbed in the Pt- or Pd-doped TiO 2 . ,, ,, This is only the case if all photons absorbed lead to hydrogen formation.…”
Section: Assesing Efficiency Factors For Hydrogen Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantum yield definition established for the photoconversion of chemical species ,,, has to be modified for hydrogen production. As reported in eq , the φ H 2 shall involve H • radicals, which are the primary chemical species leading to the formation of H 2 as follows Thus, the φ H 2 accounts for hydrogen production as a ratio of the H • radical species produced over the number of photons absorbed in the Pt- or Pd-doped TiO 2 . ,, ,, This is only the case if all photons absorbed lead to hydrogen formation.…”
Section: Assesing Efficiency Factors For Hydrogen Productionmentioning
confidence: 99%
“…They are used to calculate the energy efficiencies during the photocatalytic photoconversion or during the photocatalytic photodegradation of organic pollutants. The significance of energy efficiencies has been stressed in recent years in the scientific technical literature by our research team. ,, Proposed efficiency factors are as follows The analysis of photocatalytic processes for organic pollutant conversion showed that the maximum value to be assigned to η OH • was 1.33 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aby et al [18] published an article on how to make a nano-silver and zinc (Ag/ZnO) photocatalyst and demonstrated its elevated efficiency. The effect of photocatalyst degradation on organic pollutants such as some dyes was investigated, and it was concluded that the efficacy of ZnO <Ag / ZnO (% 1wt) <Ag / ZnO (4 wt%) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous photocatalysis is one of the advanced oxidation processes, which exhibit a significant potential for use in environmental remediation, hydrogen production and cancer treatment (de Lasa and Serrano Rosales 2009;Serrano Rosales et al 2016;Fujishima and Zhang 2006). Photocatalytic reactions are result of interaction between photons with the appropriate wavelength and a solid semiconductor (Linsebigler, Lu, and Yates 1995;Fujishima, Zhang, and Tryk 2008).…”
Section: Introductionmentioning
confidence: 99%